HEMATOTOXIC AND GENOTOXIC EFFECT OF PARAPHENYLENEDIAMINE AFTER SUBCHRONIC TOPICAL APPLICATION IN RATS - KARABI DUTTA; MANUJ KR. BHARALI (The Bioscan, 2010)
Dermal exposure and subsequent toxicity evaluation is a routine trend in toxicological research after it has been realized that skin also act as a route of exposure for xenobiotics. Para-Phenylenediamine (PPD/1, 4 diaminobenzene), a monocyclic arylamine, is widely used in almost all hair dye formulation. Systemic exposure to PPD and PPD containing hair dye has been shown to induce hypersensitivity in sensitized individual only. But in others PPD or hair dye containing PPD doesn’t elicit any negative response, thus allowing continuous use of such hair dye products containing PPD. Epidemiological studies indicated higher risk of leukemia, lymphoma and bladder cancer among user of hair dye containing PPD. In vitro studies involving PPD and its various derivatives have also been shown to cause DNA fragmentation in lymphocytes. The present study was conducted to investigate the hematological and genotoxic effect of three different doses of PPD (1, 2, 3 mg/kg) after repeated topical application for 30 days. The results of the present investigation clearly indicated hematoxicity of PPD as was evident from reduced RBC count, PCV value, Hemoglobin and increased reticulocytes in the peripheral circulation and significant changes in the cytomorphology of the blood cells. The comet assay of the peripheral blood lymphocytes of PPD treated rat’s shows significant amount of DNA damage compared to the control animal group, suggesting that PPD is genotoxic in nature.